2005
DOI: 10.1111/j.1365-2990.2005.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and reticular variants of haemangioblastoma revisited: a clinicopathologic study of 88 cases

Abstract: The presence of histological variants of haemangioblastoma is well established, but data on the prognostic implications of histological subtyping are missing. We thus characterized clinical factors associated with histological subtypes, that is, of the cellular and reticular variant of haemangioblastoma, in a series of 88 consecutive primary haemangioblastomas of the central nervous system. Ten haemangioblastomas were classified as 'cellular' according to Cushing and Bailey. As compared to the more common 'ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 9 publications
(10 reference statements)
2
35
0
Order By: Relevance
“…Histologic criteria for subclassifying a hemangioblastoma as cellular or reticular were those used by Hasselblatt et al [4]. Briefly, cellular hemangioblastomas were characterized by zellballen-like cellular clusters of uniform tumor cells with finely granular eosinophilic cytoplasm and endothelial hyperplasia, whereas the reticular subtype showed abundant capillaries and scattered stromal cells with highly vacuolated or clear cytoplasms (Fig.…”
Section: Patients and Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic criteria for subclassifying a hemangioblastoma as cellular or reticular were those used by Hasselblatt et al [4]. Briefly, cellular hemangioblastomas were characterized by zellballen-like cellular clusters of uniform tumor cells with finely granular eosinophilic cytoplasm and endothelial hyperplasia, whereas the reticular subtype showed abundant capillaries and scattered stromal cells with highly vacuolated or clear cytoplasms (Fig.…”
Section: Patients and Tumorsmentioning
confidence: 99%
“…They are characterized histologically by the 2 main components of large vacuolated stromal cells and a rich capillary network [1] and can be subclassified into 2 variants on the basis of the abundance of the stromal cell component: the rarer cellular hemangioblastomas defined by zellballen-like cellular clusters of uniform tumor cells, and the more common reticular subtype showing abundant capillaries and stromal cells [4,5]. A recent large clinicopathologic study of 88 hemangioblastomas found the cellular variant to comprise 11.4% of all hemangioblastomas and to be significantly associated with a greater probability of recurrence and a higher MIB-1 0046 proliferation index [4]. To investigate whether these 2 subtypes of capillary hemangioblastomas also differ in their cytogenetic profile and may thus provide biologically and diagnostically useful information, we carried out a comparative genomic hybridization (CGH) analysis of 10 cellular and 10 reticular hemangioblastomas.…”
Section: Introductionmentioning
confidence: 99%
“…Primary glioblastomas, however, only rarely show these genetic alterations [9]. Especially cellular hemangioblastomas show morphological similarities with glioblastomas [6]. Strong carbonic anhydrase IX staining was found in all three cases included in our control group.…”
Section: Discussionmentioning
confidence: 93%
“…Cellular hemangioblastomas are less common than the reticular kind, and they recur more frequently. 3 Hemangioblastomas present in both sporadic forms and familial forms associated with von Hippel-Lindau (VHL) disease. VHL disease is an autosomal-dominant disorder characterized by benign and malignant tumors mostly seen in the retina, kidney, adrenal gland, pancreas, and epididymis, in addition to central nervous system hemangioblastomas.…”
Section: Introductionmentioning
confidence: 99%